The Political Pedagogical Project in a collective perspective (Research, Society and Development, 2020)
This article presents the results of a study on the construction process of the Political-Pedagogical Project (PPP) carried out at a school in Quixadá / Ce. This document indicates a path to be followed explicitly by a school. The objective was to investigate how the development of this educational policy, the PPP, takes place, given the Brazilian educational context that has been launched in recent years and what is its connection with the school reality examined. The adopted methodology was a case study, with essential sources guided by the qualitative research in the analysis of the data, the structured questionnaire and the focus group were used as instrument, articulated with the available theoretical framework on the theme. In this research, we spoke with Ilma Passos Alencastro Veiga, the main theorist in deepening the theme. The results of the investigation announce that the PPP is connected to the school unit, but for it to be effectively elaborated and / or executed, with the full participation of the educational community, operating in a democratic manner with the involvement of the various segments, in a way that it will contribute for the pedagogical work of the teaching unit.